One space: Shared visual scenes for active free play - COHEN, Maayan (Institutional Knowledge at Singapore Management University, 2014)
Children engage in free play for emotional, physical and social development; researchers have explored supporting free play between physically remote playmates using videoconferencing tools. We show that the configuration of the video conferencing setup affects play. Specifically, we show that a shared visual scene configuration promotes fundamentally active forms of engaged, co-operative play.